2011
DOI: 10.1364/oe.19.010714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nonlinear absorptivity in internal modification of bulk glass by ultrashort laser pulses

Abstract: Thermal conduction model is presented, by which nonlinear absorptivity of ultrashort laser pulses in internal modification of bulk glass is simulated. The simulated nonlinear absorptivity agrees with experimental values with maximum uncertainty of  3% in a wide range of laser parameters at 10ps pulse duration in borosilicate glass. The nonlinear absorptivity increases with increasing energy and repetition rate of the laser pulse, reaching as high as 90%. The increase in the average absorbed laser power is acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 21 publications
3
69
0
Order By: Relevance
“…An experimental demonstration of reduced damage threshold in fused silica with temperature was found in [14]. More recently, observation of induced absorption in glasses due to ultrashort laser pulse exposure has also been reported [20]. Additionally, recent density-functional theory calculations [21] have shown that silica absorption spectra are expected to exhibit exponential tails near the band edge at elevated tempertatures.…”
Section: Introductionmentioning
confidence: 92%
“…An experimental demonstration of reduced damage threshold in fused silica with temperature was found in [14]. More recently, observation of induced absorption in glasses due to ultrashort laser pulse exposure has also been reported [20]. Additionally, recent density-functional theory calculations [21] have shown that silica absorption spectra are expected to exhibit exponential tails near the band edge at elevated tempertatures.…”
Section: Introductionmentioning
confidence: 92%
“…The transmitted pulse energy Q t on the backside was measured with the power meter ( Figure 1) and compared to the pulse energy Q 0 with no sample in between. The nonlinear absorption A exp was calculated with [12] ( )…”
Section: Absorption Curves Of Lasmentioning
confidence: 99%
“…The laser parameters like peak power and pulse repetition rate of the ultra-short pulse laser is significant to control the width and depth of heating as well as the changes of mode i.e. laser ablation to laser welding or vice versa [7].…”
Section: Introductionmentioning
confidence: 99%
“…In fusion welding of transparent material, the laser energy is absorbed by nonlinear process with multiphoton ionization followed by avalanche ionization and the absorbed laser energy in the free electrons is transferred to the lattice to provide the temperature field in bulk glass [2,7]. Internal modification at high pulse repetition rates is due to heat accumulation effect.…”
Section: Introductionmentioning
confidence: 99%